Econometric Analysis of the Relationships Between Growth, Exports and Energy Exports in Azerbaijan - Huseynli, Nigar (International Journal of Energy Economics and Policy, 2022)
The place of exports in the economic development of a country has a very important share. Whether in developed or developing countries, the demand for energy makes energy exports important in exports. In this study, the relationship between the economic growth of Azerbaijan, the total amount of exports and energy exports has been tried to be determined. The data for the analysis were obtained from the Azerbaijan State Statistics Institute on an annual basis. Eviews.5 for performing the analysis program has been used. After taking the logarithmic values of the data, the data were made stationary, the appropriate lag lengths were found, and then they were subjected to the Granger causality test. Correlation relationships were also examined in order to measure the strength of the relationship between the data.